Optimizing the Allocation of Resources among HIV Prevention Interventions in Honduras - Beeharry, Girindre; Schwab, Nicole; Akhavan, Dariush; Hernández, Rosalinda; Paredes, Carla (World Bank, Washington, DC, 2013)
This paper presents a model that policymakers can use to determine the resource allocation that will prevent the maximum number of new HIV infections at any given budget level. The optimal allocation exercise was conducted in Honduras, where the epidemic is still concentrated in high-risk groups but has begun spreading into the general population. Most transmissions occur through heterosexual sex, followed by sex between men, and mother-to-child transmission. Adult prevalence is estimated at 1.4 percent. The optimization exercise involves several steps:(a) choosing population subgroups targeted for intervention; (b) estimating the proportion of each subgroup that can be reached; (c) estimating the total number of new infections expected in each subpopulation; (d) defining the set of HIV prevention interventions to be considered; (e) estimating the unit cost of each intervention; and (f) estimating the expected effectiveness of each intervention. Most of the data required to run the model has to be guesstimated or derived from the literature. To address this challenge, a group of some forty local and international experts in HIV/AIDS met in Tegucigalpa in May 2002 and arrived at the consensus estimates used in this exercise. They based their estimates on data submitted by two local epidemiologists who had conducted an extensive literature search prior to the workshop. The results from this collective exercise show that for limited HIV prevention budgets (below $500,000), condom social marketing and condom distribution prevent the maximum number of HIV infections. If the HIV prevention budget is between $750,000 and $2.5 million, then Information Education and Communication (IEC) targeted at high risk groups, HIV counseling and access to rapid testing, and an information, education and communications strategy (IEC) for the Garifunas should also be part of the country's prevention strategy. The exercise shows that some prevention interventions are unattractive even when the HIV prevention budget increases to $10 million..